Pengaruh Penerapan Metode Active Learning Terhadap Motivasi Belajar Siswa Kelas V Di SD Negeri 157 Palembang - Fitasari, Silvi Ike; Nurlaila, Nurlaila; Fatimah, Siti; Maryamah, Maryamah; Shawmi, Ayu Nur (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to determine the effect of the application of active learning methods on the learning motivation of fifth-grade students at SD Negeri 157 Palembang. This type of research is an experimental study with a true experimental design and a pretest-posttest control group design. The researcher used this type of research to see whether there is an effect caused by the application of active learning methods on students' learning motivation. In its implementation, this study used two classes, namely the experimental class and the control class. The sample in this study was determined using cluster sampling techniques. In cluster sampling, the population is divided into groups or clusters, and several clusters are selected randomly. Then, all members of the selected clusters are taken as samples. The data collection technique in this study is in the form of distributing questionnaires and documentation, and the data analysis technique is validity, reliability, and hypothesis testing (t-test) using SPSS IBM version 26 for windows. The results of the analysis show a sig. value of 0.000